Sytuacja dorosłych osób z niepełnosprawnościami przebywających pod opieką domu pomocy społecznej (ze szczególnym uwzględnieniem osób z niepełnosprawnością wzroku) = The situation of adults with disabilities staying under the care of a social welfare home (with particular emphasis on people with visual impairments) - Zaorska, Marzenna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents considerations on the life situation of people with disabilities (with particular emphasis on people with visual impairments) staying under the care of a social welfare home dedicated to the disabled community. They concern both positive aspects of institutional care and selected problems related to the individual, social and even professional activation of the residents of such facilities. Additionally, the implemented discourse was incorporated into selected provisions of Polish law and the ?UN Convention on the Rights of Persons with Disabilities? (2006, 2012) in the context of observing and failing to observe the rights of residents of 24-hour care facilities. The basis for the analyses is the situation of people with disabilities staying in the Social Welfare Home of the Polish Association of the Blind in Olsztyn.
Keywords: dom pomocy społecznej; dom pomocy społecznej dla osób z niepełnosprawnościami; dom pomocy społecznej dla osób z niepełnosprawnością wzroku; social welfare home; social welfare home for people with disabilities; social welfare home for people with visual impairments